2020
DOI: 10.1089/apc.2019.0198
|View full text |Cite
|
Sign up to set email alerts
|

Virological Outcome After Choice of Antiretroviral Regimen Guided by Proviral HIV-1 DNA Genotyping in a Real-Life Cohort of HIV-Infected Patients

Abstract: Issues have been raised concerning clinical relevance of HIV-1 proviral DNA genotypic resistance test (DNA GRT). To assess impact of DNA GRT on choice of antiretroviral therapy (ART) and subsequent virological outcome, we retrospectively reviewed decision-making and viral load (VL) evolution following DNA GRT performed in our center between January 2012 and December 2017, except those prescribed within the framework of a clinical trial. A total of 304 DNA GRTs were included, 185 (62%) performed in a context of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Furthermore, a recent retrospective observational study demonstrated that DNA genotype-guided regimen changes were well tolerated with no increased risk of virologic failure [ 42 ]. In a similar study conducted in France, DNA genotype-guided regimen changes increased the probability of maintaining viral suppression; however, the inclusion of APOBEC-mediated hypermutated sequences in their dataset confounds interpretation [ 43 ]. As GenoSure Archive removes hypermutated sequences from assay results, our dataset does not over-report resistance substitutions caused by hypermutation, such as M184I, which was detected at low frequency (1%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent retrospective observational study demonstrated that DNA genotype-guided regimen changes were well tolerated with no increased risk of virologic failure [ 42 ]. In a similar study conducted in France, DNA genotype-guided regimen changes increased the probability of maintaining viral suppression; however, the inclusion of APOBEC-mediated hypermutated sequences in their dataset confounds interpretation [ 43 ]. As GenoSure Archive removes hypermutated sequences from assay results, our dataset does not over-report resistance substitutions caused by hypermutation, such as M184I, which was detected at low frequency (1%).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent retrospective observational study demonstrated that DNA genotype-guided regimen changes were well tolerated with no increased risk of virologic failure [42]. In a similar study conducted in France, DNA genotype-guided regimen changes increased the probability of maintaining viral suppression; however, the inclusion of APOBEC-mediated hypermutated sequences in their dataset confounds interpretation [43].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that HIV DNA sequencing may provide value for decision-making for selected patients, including those with multiple previous or foreseen ART adjustments due to comorbidities, medication interactions, difficulty accessing care, hesitancy regarding ART switches or other factors that could increase risk when switching therapy. Maybeck et al also provided cohort data in support of HIV DNA sequencing to guide treatment decisions alongside historical data based on plasma HIV RNA sequencing [ 36 ]. Armenia et al found that among virologically suppressed patients, detection of RAMs in HIV DNA, together with a low nadir CD4 cell count and a short duration of virological control, was predictive of virological rebound after switching therapy [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…A general limitation of all of the currently available and future candidate markers is the almost exclusive application to the blood compartment. While the analysis of blood markers has clearly allowed establishment of highly effective treatment strategies, the vast majority of HIV species reside in lymphatic tissue in multiple anatomical sites that are hardly accessible [31]. Although blood will necessarily remain the material of choice in routine patient management, studies addressing the added value of sampling these sites are required to gain a full profile of the HIV reservoir and its dynamics under different treatment strategies.…”
Section: Perspectivesmentioning
confidence: 99%